2021
DOI: 10.3389/fevo.2020.608289
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Polymorphic Melanic Side-Spotting Patterns in Poeciliid Fishes

Abstract: Melanin-based color patterns are an emerging model for studying molecular and evolutionary mechanisms driving phenotypic correlations. Extensive literature exists on color patterns and their correlated traits in the family Poeciliidae, indicating that these fishes are tractable models. We review the biology of polymorphic melanic side-spotting patterns characterized by macromelanophores forming irregular spotted patterns across fishes’ flanks. These patterns are present in the genera Gambusia, Limia, Phallocer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 120 publications
(388 reference statements)
0
8
0
Order By: Relevance
“…vittata. It has been shown that characteristics of the physical environment where fish species live can play an important role in changing the frequencies of melanistic morphs temporally and spatially (Horth & Travis, 2002;Zerulla & Stoddard, 2021). For instance, in the Green Swordtail (Xiphophorus hellerii) and the Atlantic Molly (Poecilia F I G U R E 5 Representation of the linear regression analysis between the size of the fish and spotted area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…vittata. It has been shown that characteristics of the physical environment where fish species live can play an important role in changing the frequencies of melanistic morphs temporally and spatially (Horth & Travis, 2002;Zerulla & Stoddard, 2021). For instance, in the Green Swordtail (Xiphophorus hellerii) and the Atlantic Molly (Poecilia F I G U R E 5 Representation of the linear regression analysis between the size of the fish and spotted area.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the most colorful morphs were the most conspicuous morphs to predators (Hurtado-Gonzalez et al, 2014). However, in the specific case of melanic side-spotting pattern background matching has not been thoroughly studied (Zerulla & Stoddard, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the apparent color pattern has a teratological cause or is subject to interspecific variations. Recent studies of melanin variations in fish have investigated fishes living in the photic zone (Zerulla & Stoddard, 2021) or have discussed melanin loss or nonsense mutations (Bian et al, 2021) but these studies may not explain the phenomenon observed in the photographs of live Leucicorus specimens. We did notice that the specimens with color signature on the trunk more commonly occur in the Eastand Central-Pacific while the uniformly light-colored ones have been seen mainly in the Central-and West-Pacific.…”
Section: Live Observationsmentioning
confidence: 99%